Analisis Brand Association Pada Produk Kecap Bango - Wiwit Rohaeni Yulianti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to find out and analyze the Brand Association of Bango Soy Sauce Products. This research method uses a quantitative approach with multiple linear regression analysis techniques processed using SPSS version 25. The data collection technique is by distributing questionnaires to 95 people as respondents through google forms. The results showed that the basis for purchasing decisions by consumers towards Kecap Bango products was determined by Delicious taste to be a cooking raw material, Quality cooking raw materials, Using quality soybeans, Comfortable in consumption, Easy to get in stores, More familiar than other soy sauce products and Superior to other products.